In vitro antibacterial effect of Caesalpinia spinosa (tara) at different concentrations on Lactobacillus acidophilus - Bornaz Acosta, Juan Guillermo (2022)
Objective: To evaluate the efficacy of Caesalpinia spinosa (tara) in different concentrations on Lactobacillus acidophilus. Material and methods: A seeding of the strain ATCC® 4356 (Lactobacillus acidophilus), was activated in thioglycolate broth in the 9 % CO anaerobic 2 chamber, where it was incubated at 37 °C for 24 hours. Then, the preparation was done in plates of Agar rogosa, it was expected to solidify and proceeded to do the seeding by surface with a micropipette. 1 ml of the strain reactivated in thioglycolate broth was taken and poured and spread with the digralsky spatula on the surface of the agar. Five 5 mm sensidisks were placed at five separate points in the Petri dish, each sensitivity was embedded with 30 microlitres with each control substance and ethanolic extract of Caesalpinia espinosa (tare), 100 % 60 % 40 % for each substance, 5 samples were used; plates were then incubated in the anaerobic chamber at 9 % CO , 37 °C, measures were 2 subsequently taken at 24 and 48 of the resulting inhibitory halo. Five study groups were formed, the first three with Caesalpinia spinosa in their different concentrations, the fourth was the 2 % Chlorhexidine Gluconate and the fifth corresponded to Amoxicillin. Results: Caesalpinia spinosa (tara) at the concentration of 100 % was the best, compared to the others studied (40 and 60 %), at 24 and 48 hours of exposure. The average measurement of the inhibitory halo of Caesalpinia spinosa at 100% was higher than that formed by chlorhexidine gluconate, Student T was applied (p < 0,05) and statistically significant difference was found between data obtained for different substances. Caesalpinia spinosa (tara) at 100 % is as competitive as 2 % Chlorhexidine Gluconate at 24 and 48 hours; but, it is lower compared to amoxicillin at these two times. Conclusion: Caesalpinia spinosa, showed antibacterial effect against Lactobacillus acidophilus, its measures were varied and in the majority superior to the Gluconate of chlorhexidine.